The adamant adherence to a prior belief: the case of anosognosia in anorexia nervosa - Rushani, Stelina; Salvato, Gerardo; Sellitto, Manuela (Frontiers in Neurology, 2025)
Anorexia Nervosa (AN) is a complex psychiatric disorder marked by restrictive eating and distorted body image. Often, individuals with AN show a persistent denial of illness severity, even in the presence of their pathology’s life-threatening consequences. This condition, known as anosognosia, has been extensively investigated in right-brain damaged patients who deny their contralesional motor deficit (anosognosia for hemiplegia; AHP). In the present perspective, we draw parallels with AHP in the attempt to explain anosognosia for the illness in AN through the most recent theoretical computational accounts. We review evidence suggesting that anosognosia in AN may be rooted in unbalanced prediction error and suboptimal multisensory integration mechanisms. Specifically, individuals with AN would normally rely more heavily on exteroceptive information at the expense of signals coming from the inside of the body—i.e., interoception—, in addition to which a distorted body memory overrides new incoming sensory information, leading to inadequate updated body image. These disrupted processes potentially involve dysfunctional insular, striatal, and prefrontal regions, whereby alterations in the dopaminergic reward system may reinforce maladaptive behaviors and attenuate responses to updating feedback. We propose a neurocognitive model according to which individuals with AN would rely excessively on outdated third-person body representations, failing to integrate new egocentric sensory cues. This perspective may offer ideas for future applications in cognitive rehabilitation of AN.